Probiotics improve intestinal oxidative stress to protect intestinal barrier function in uremic rats - WEI Meng; JIANG Hong-li; SHI Ke-hui; WANG Meng; SUN Ling-shuang; HE Quan (Linchuang shenzangbing zazhi)
Objective To investigate whether oral probiotic Bifidobacterium animalis subsp.Lactis Bi-07 protects the intestinal barrier function of uremic rats,and explore whether it plays its biological effects by improving oxidative stress in tissues.Methods Thirty SD rats were randomly divided into 3 groups(n=10),sham operation group,uremic group,uremia + probiotic group.For the sham operation group only the renal capsule was opened,and for the uremic group 5/6 nephrectomy was conducted.For the uremia + probiotic group 5/6 nephrectomy was performed and then the animals were administered with Bi-07 every day for 4 weeks.The rats were anesthetized and the jejunum,ileum and colon segments were taken out.The ultrastructure of the intestinal epithelial tight junction complex was observed by scanning electron microscopy combined with lanthanum nitrate staining.The intestinal homogenate was prepared,and malondialdehyde(MDA) content was determined by thiobarbituric acid condensation method;and superoxide dismutase(SOD) activity was determined by xanthine oxidase method.Results Compared with the uremic group,supplement of probiotics could restore the tight junction ultrastructure between epithelial cells,with neat microvilli and intact structure.Compared with the uremic group,the intestinal permeability in the uremia + probiotic group was significantly decreased(P<0.05);serum inflammatory factors hs-CRP,IL-6,TNF-α levels were significantly lower(P<0.05);the intestinal SOD level was significantly increased(P<0.05);and the intestinal MDA showed a decreasing trend,but the difference was not statistically significant(P>0.05).Conclusions Bi-07 can improve intestinal barrier function in uremic rats.The mechanism may be realized by inhibiting intestinal oxidative stress so as to reduce intestinal barrier damage in uremic rats.